An efficient privacy preserving Pub–Sub system for ubiquitous computing. (15th January 2013) - Tian, Yuan; Song, Biao; Hassan, Mohammad Mehedi; Huh, Eui–nam
The Pub/Sub middleware has gained a lot of attention in the design and development of ubiquitous applications. The issue of privacy is of serious concern for applying the Pub/Sub to ubiquitous computing. The design of the privacy mechanism should consider the required efficiency of event dissemination in the underlying Pub/Sub middleware. In this paper, we address these challenges among ubiquitous applications by applying the proposed privacy–aware Pub/Sub middleware, which provides high performance and scalability with parameterised and prioritised attributes. It is able to provide fast and dynamic privacy management with low extra overhead.